PENGARUH KONSELING KELOMPOK DENGAN TEKNIK MINDFULNESS DALAM MENGURANGI BURNOUT AKADEMIK PADA MAHASANTRI SEMESTER AKHIR DI PONDOK PESANTREN AL-QUR’AN IBNU KATSIR 1 JEMBER - Madhani, Miftah Ismatullah; Nasruliyah Hikmatul Maghfiroh; Imaratul Ulwiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effect of group counseling using mindfulness techniques in reducing academic burnout among final-year students at Pondok Pesantren Al-Qur’an Ibnu Katsir 1 Jember. Purposive sampling was used to select the research sample. This study employed a quantitative method with a pre-experimental design using One Group Pre-Test Post-Test. Data analysis was conducted using the Wilcoxon test with SPSS version 25.0. The Wilcoxon test results showed a Z value of -1.826 with a two-tailed Asymp. Sig of 0.068. Since the Asymp. Sig (2-tailed) > 0.05, it can be concluded that Ha is accepted, indicating that group counseling with mindfulness techniques effectively reduces academic burnout among final-year students at Pondok Pesantren Al-Qur’an Ibnu Katsir 1 Jember.